2014
DOI: 10.1001/jamainternmed.2014.5271
|View full text |Cite
|
Sign up to set email alerts
|

Communication About Serious Illness Care Goals

Abstract: ffective communication plays a major role in facilitating adaptation to illness realities, appropriate decision making, and quality of life 1,2 throughout the trajectory of a serious illness. As patients approach the end of life, communication about goals of care and planning is a key element in helping assure that patients receive the care they want, in alleviating anxiety, and in supporting families. [3][4][5] Effective communication supports, not only endof-life care, but quality of life throughout the illn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
448
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 1,068 publications
(507 citation statements)
references
References 102 publications
7
448
1
Order By: Relevance
“…However, there is consistent evidence that clinicians struggle to convey information, check understanding, and engage patients in decision making 1516. The lack of any effective feedback about performance makes it difficult to improve.…”
Section: Potential Role In Communication With Patientsmentioning
confidence: 99%
“…However, there is consistent evidence that clinicians struggle to convey information, check understanding, and engage patients in decision making 1516. The lack of any effective feedback about performance makes it difficult to improve.…”
Section: Potential Role In Communication With Patientsmentioning
confidence: 99%
“…Advanced communication skills are essential for healthcare providers working in this setting [16,17]. Various studies have shown the positive effects of communication training on patients' quality of life as well as improvements in job satisfaction and a decrease in burden for healthcare professionals [18,19,20].…”
Section: Communication In Advanced Cancermentioning
confidence: 99%
“…Dunlay & Strand (2016) created a framework for conducting goals of care discussions that consisted of: 1) reviewing previous discussions, 2) assessing patient willingness and preferred role, 3) discussing prognosis and anticipated outcomes, 4) asking patient values, goals, fears, 5) discussing unacceptable health states, 6) discussing life sustaining preferences, 7) summarizing and make a plan, 8) complete/updating advanced directives and document conversations in electronic medical record. This framework also highlights the use of communication strategies used to understand patient perception, allow for sharing of information, and responding in an empathetic manner.…”
Section: Framework and Protocolsmentioning
confidence: 99%
“…This protocol provides a communication based, skillstraining framework that medical professionals can develop and utilize in practice. Bernacki et al (2014) synthesized a narrative review and recommendations relating to goals of care highlighting patient, physician, and system factors contributing to these discussions. These authors concluded that a delay in discussions leads to poorer outcomes.…”
Section: Framework and Protocolsmentioning
confidence: 99%
See 1 more Smart Citation